2005
DOI: 10.1111/j.1463-5224.2005.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural findings in feline corneal sequestra

Abstract: Apoptosis may play a role in the pathogenesis of feline corneal sequestration independent of the presence of DNA of these infectious organisms. Prospective clinical studies are warranted to further understand the significance of T. gondii in relation to feline corneal sequestration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 24 publications
1
37
1
5
Order By: Relevance
“…Previous studies have also tried to elucidate the source of the brown color of sequestra in hopes of determining the exact pathogenesis of sequestrum formation. Feline herpes virus‐1 has been proposed to play a role, but cats with sequestra are not consistently herpes positive by PCR, and many unaffected cats are positive for herpes 2,13–16 . Tear film break‐up times and goblet cell numbers in the conjunctiva of normal and affected cats have been evaluated and are similar 16 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have also tried to elucidate the source of the brown color of sequestra in hopes of determining the exact pathogenesis of sequestrum formation. Feline herpes virus‐1 has been proposed to play a role, but cats with sequestra are not consistently herpes positive by PCR, and many unaffected cats are positive for herpes 2,13–16 . Tear film break‐up times and goblet cell numbers in the conjunctiva of normal and affected cats have been evaluated and are similar 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In the past some have believed this pigment to be iron, but both a normal cornea and three sequestra had very low levels of iron 17,18 . One study used optical microscopy to examine the sequestra and concluded that the dark particles seen were consistent with melanin, but this was not supported by an electron microscopy study 15,17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…hereditary [1], feline herpes Virus -1 [2,3] conformational, tear film abnormalities [4][5][6], Toxoplasma gondii [7] but it is most commonly associated with ocular injury and inflammation [4,8]. The condition is a distinctive corneal lesion observed particularly in felines [9].…”
Section: Introductionmentioning
confidence: 99%